Study on Sunshine Stress Effect of Long-Span and Wide Concrete Box Girder. (31st May 2022) - Cheng, Wang; Chentian, Zhang; Shuo, Li; Jianhua, Li
Abstract : In order to further clarify the sunshine stress effect of long-span and wide concrete box girder, the study selected a concrete box girder with 4 × 42 m span and 33.5 m width, formed the temperature field load through a field test and numerical simulation, established a numerical analysis model by using the finite element program of ANSYS, and comprehensively analyzed the longitudinal temperature stress distribution of a long-span and wide concrete box girder under sunshine. The midspan section of the first span of the box girder is selected for field stress measure, and the field measure results and numerical analysis results are compared and analyzed. The research shows that the results of field measurement and numerical simulation are basically consistent. Sunshine temperature has a great influence on long-span and wide concrete box girder, which should be paid enough attention.